Nail as a window of systemic diseases - Archana Singal; Rahul Arora (Wolters Kluwer Medknow Publications, 2015)
Certain nail changes are specific for various dermatological disorders. In addition, examination of nails may also provide an insight into more sinister systemic manifestations in the form of both subtle as well as specific changes. These findings may present as a defect of various anatomical components of the nail unit; nail matrix, nail plate and/or nail bed or vasculature. This article is an attempt to equip the dermatologists with a foresight to suspect and diagnose the unapparent systemic connotations that may be possible by a simple but detailed nail examination.